Effects of the conditions of frozen storage and freeze-thaw treatment on the formation of α-dicarbonyl compounds in unwashed silver carp surimi - SU Jie; LI Jiayi; LIU Yongle; ZHOU Jinsong; HUANG Yiqun; LI Xianghong; WANG Faxiang (Shipin yu jixie)
ObjectiveTo regulate the formation of α-dicarbonyl compounds (α-DCs) in unwashed silver carp surimi.MethodsThe levels of 3-deoxyglucosaldosterone (3-DG), glyoxal (GO), pyroacetal (MGO) and 2, 3-butanedione (2,3-BD) were analyzed in surimi during frozen storage and freeze-thaw cycles at -18 ℃ and -60 ℃. The effects of freezing temperature, freezing method, and the addition of an antifreeze agent (enzymatic hydrolysis product of silver carp) on the formation of these α-DCs were evaluated.ResultsAfter 60 days of storage at -60 ℃, the levels of 3-DG, MGO and 2,3-BD increased by 209%, 122% and 139%, respectively, but were significantly lower compared to storage at -18 ℃. GO levels initially increased, peaking on day 45 during -60 ℃ storage, with a slower rate of change compared to the -18 ℃ group, which peaked on day 30. These findings indicate that ultra-low temperature storage can effectively reduce α-DCs formation. During freeze-thaw cycles, 3-DG and 2,3-BD levels increased progressively with more cycles, while GO and MGO levels initially increased and later declined. Freezing at -60 ℃ notably inhibited α-DC formation, whereas other freezing methods and temperature showed no significant effects. Adding enzymatic hydrolysates from silver carp suppressed increases in GO, MGO and 2,3-BD after 3 freeze-thaw cycles and mitigated declines in GO and MGO after 6 cycles.ConclusionThe addition of antifreeze agents can partially inhibit the formation and transformation of α-DCs, especially under repeated freeze-thaw conditions.